Social Protection for a Changing India : Main Report - World Bank (World Bank, 2012)
India's surge in growth and rapid expansion in public spending in the past decade has created new possibilities for its social protection system. The growing importance of social protection (SP) is reflected in the Government of India (GoI) common minimum program and eleventh five year plan which commit to institutionalization of programs as legal rights (as in the case of public works, through the national rural employment guarantee act), continued up-scaling of interventions (e.g., social pensions and midday meals), and proposals to expand new types of SP interventions to the large unorganized sector (e.g., social security). The report draws on existing and new data sources,. including analysis of: (i) administrative data; (ii) several rounds of the National Sample Survey (NSS) data; (iii) a social protection survey (SPS) undertaken for this report in 2006 in rural areas of Orissa, Madhya Pradesh, and Karnataka; (iv) dedicated surveys on social pensions in Karnataka (KSPS) and Rajasthan (RSPS) in 2005 and 2006 respectively; and (v) a living standards survey conducted in Jharkhand in 2005 (JLSS). In addition, the report incorporates a rich body of secondary sources on SP program performance and impact by national researchers and government agencies.